Ferroptosis-like cell death associated with Vibrio parahaemolyticus infection in the clam Meretrix petechialis - Shujing Zhang; Fengxia Xu; Mengyao Gao; Yu Cui; Yuling Dong; Shuang Jiao; Changjian Xie; Iseult Lynch; Zhiling Guo; Qiuxiang Pang (Fish & Shellfish Immunology, 2026)

An FcRn-mediated exosome-based oral vaccine enhanced co-mucosal immunity via targeting intestinal epithelial transport and lymphatic activation - Wei Zhang; Wen Guo; Caishun Chen; Meiqi Han; Yuling Mao; Siling Wang (Chemical Engineering Journal, 2026)

Platinum accumulation in chemotherapy: toxicity mechanisms, challenges, and mitigation strategies - Yier Lai; Guodong Qiu; Zhiwei Zheng; Xiaoting Huang; Pi Guo; Yuling Zhang; Ling Fang (BioMetals, 2026)
Platinum-based chemotherapeutic agents constitute the cornerstone of treatment for a wide range of solid tumors. However, residual platinum can persist in the body long after treatment cessation, leading to progressive accumulation, chronic multi-system toxicity, and significant impairment of patients' quality of life. The insidious onset and lack of specific monitoring methods often lead to the oversight of this treatment-related metal accumulation toxicity. This article reviews the environmental and occupational exposure risks of platinum, its unique pharmacokinetic properties, and elucidates how its irreversible binding to proteins and accumulation within mitochondria form the chemical basis for its long-term toxicity. It further elaborates on the core mechanisms underlying platinum accumulation-mediated multi-organ toxicity, including nephrotoxicity, neurotoxicity, and ototoxicity. The aim is to provide insights and directions for improving the long-term prognosis of cancer survivors by clarifying the toxicological mechanisms, clinical impacts, and future strategies for mitigating platinum-induced metal accumulation.

Consistent functional genes in methanogens along soil profiles in a temperate marshland - Yuling Tan; Nannan Wang; Kexin Li; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ming Yang; Wenwen Tan; Yuedong Guo; Yanyu Song; Fenghui Yuan; Xiaofeng Xu; et al. (Soil Ecology Letters, 2026)

Associations of pedogenic carbonate accumulation with soil organic-inorganic carbon coupling in arid croplands - Tongping Lu; Yuling Li; Xuhui Wang; Hui Guo; Bin He; Muhammad Shoaib Rana; Jie Ma; Changyan Tian; Jianfei Shi; Yugang Wang; Xiujun Wang (Agriculture, Ecosystems & Environment, 2026)

Unveiling forest vertical structure across China through stratified effective plant area index using extensive UAV LiDAR and multi-source remote sensing data - Zhiyong Qi; Zitong Bai; Haitao Yang; Yao Wang; Kai Cheng; Zekun Yang; Ang Chen; Tianyu Xiang; Yu Ren; Yixuan Zhang; Yuling Chen; Qingpeng Wang; et al. (Remote Sensing of Environment, 2026)

Preliminary insight into the ability of bovine-derived Loigolactobacillus coryniformis XJ-C-L1-produced acid-dependent extracellular metabolites to inhibit MRSA growth and biofilm formation in milk - Yuling Guo; Wenjing Wang; Yaqian Liang; Meihui Tian; Ming Wu; Junkai Wang; Haihong Hao; Yu Pan (International Dairy Journal, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Seawater eDNA and Underwater Visual Surveys Reveal Genus-Level Reef-Building Coral Communities in the Wanshan Archipelago, South China Sea - Jiabin Guo; Lan Yang; Zhihui Qin; Anxin Lu; Yuling Ma; Yue Zheng; Biao Chen; Zhenjun Qin; Zhiheng Liao; Lijia Xu; Yongzhi Wang; Kefu Yu; et al. (Fishes, 2026)
Environmental DNA (eDNA) metabarcoding is increasingly used as a complementary tool for coral biodiversity assessment, but its performance in subtropical, estuary-influenced reef systems remains insufficiently tested. This study combined seawater eDNA metabarcoding with concurrent underwater visual surveys and historical records to assess reef-building scleractinian corals in the Wanshan Archipelago, Pearl River Estuary. In June 2022, surface and bottom seawater samples were collected from seven sites, yielding 14 eDNA samples, and dive-based photographic surveys were conducted concurrently. A universal 18S rRNA assay was used for high-throughput sequencing, and eDNA detections were compared with visual and historical survey data at the genus level. eDNA detected 13 families and 21 genera, with Porites and Echinopora as dominant genera. eDNA recovered more genera than concurrent visual surveys in all five regional comparisons, although the two methods yielded overlapping but partly distinct genus inventories. Surface-water eDNA showed a slight, site-dependent advantage in genus recovery and overlap with concurrent visual surveys, whereas correspondence with historical records varied among regions; surface and bottom samples shared most genera but also contributed complementary layer-specific detections. Community composition showed spatial clustering broadly consistent with geographic proximity. These findings indicate that seawater eDNA provides complementary genus-level information and support paired surface- and bottom-water sampling for a more complete exploratory characterization of coral diversity in complex subtropical coastal reef systems.

Mussel-inspired engineering of green spherical cellulose adsorbents with PEI/PDA multilayers for efficient and selective mercury capture - Ming Li; Yuxin Gong; Xiaofei Fan; Jianing Hu; Shiwei Guo; Yuling Zhang; Huining Xiao (Desalination, 2026)

Camel milk-derived Lentilactobacillus parabuchneri L-185 produces acid-associated metabolites that inhibit MRSA growth and biofilm formation in milk - Wenjing Wang; Yuling Guo; Junkai Wang; Yaqian Liang; Meihui Tian; Yitao Li; Hui Zhang; Haihong Hao (International Journal of Food Microbiology, 2026)

Antifungal activity and mechanisms of honokiol against Fusarium fujikuroi, the Chinese yew leaf blight pathogen - Yuling Jiang; Yao Charles Meto; Amir Khan; Zhenxiang Guo; Anlong Hu (Physiological and Molecular Plant Pathology, 2026)

A two-wave panel biomonitoring study of changes in urinary pesticide metabolites and their associations with liver function and inflammatory markers - Dandan Liu; Xiaotong Li; Yuling Chen; Fenfang Deng; Jia He; Chongshan Guo; Jun Yuan; Lei Tan (Environmental Research, 2026)

Shoot apical meristem-dependent adventitious bud induction from embryo axes of castor bean (Ricinus communis L.) via optimized cytokinin-auxin ratio - Liang Bai; Liying Shan; Jian Song; Mengchen Xu; Yue Wang; Ruiyan Guo; Yanli Jin; Yangguang Duan; Yuling Zhang; Zhimin Jiang; Jilong Zhong; Yan Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

A novel antiviral peptide Laby A1/A3 precursor-SUMO against PCV2 replication with broad-spectrum antiviral potential - Yan Zhang; Yuling Li; Qiqi Xia; Jingyuan Zhang; Yanmin Li; Long Zhou; Zijing Guo; Zhidong Zhang (Veterinary Microbiology, 2026)

Interpretable machine learning model based on floc images for monitoring the coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Peng Guo; Chuanchuan Dou; Wangben Zhao (Process Safety and Environmental Protection, 2026)

Biochar and moisture variability shape soil carbon pools via microbial carbon-degrading genes - Yue Pan; Tingting Tan; Jie Meng; Hongpeng Guo; Yingbo Dong; Yukui Cui; Na Yu; Xinxin Jin; Yuling Zhang; Hongtao Zou; Nanthi Bolan; Kadambot H.M. Siddique (Journal of Environmental Management, 2026)

Revealing the spatial distribution of crown base height across China based on close-range Lidar data - Zekun Yang; Zhiyong Qi; Yuling Chen; Kai Cheng; Haitao Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Yu Ren; Weiyan Liu; Danyang Lin; Guoran Huang; et al. (Remote Sensing of Environment, 2025)

Synthesis of guanylhydrazone functionalized tetraphenylethylene for combating antibiotic resistance and biofilms - Shuwen Guo; Zijun Chen; Yuling He; Haipeng Xu; Yuwei Zhao; Ye Yang; Peng Yang (Chemical Engineering Journal, 2025)

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

Dam operation changed the transport patterns of microplastics - from a global perspective - Yuling Chen; Li Lin; Yi Li; Yu Gao; Lei Dong; Xiong Pan; Ziwei Guo (Environmental Pollution, 2025)

Efficient large-scale vegetation mapping at the formation level using multi-source data: A case study in Beijing, China - Jiachen Xu; Yongmei Huang; Kai Cheng; Yi Wang; Tianyu Hu; Hongcan Guan; Yuling Chen; Yu Ren; Mengxi Chen; Zekun Yang; Jiarui Wang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Encapsulation of cinnamaldehyde with protein-based nanoemulsions for strawberry preservation: Influence of protein types - Jiayan Lu; Yunyan Hua; Mengjia Guo; Laixue Ni; Yuling Cai; Yungang Cao; Longfeng Wang; Weiwei Li (Food Packaging and Shelf Life, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Development of a model for maize stalk lodging resistance based on plant bending strength and trait selection - Guanmin Huang; Yuling Guo; Weiming Tan; Mingcai Zhang; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Field Crops Research, 2025)

Comparative transcriptomic analysis of heterotic maize development during kernel filling - Wenyu Li; Xiangkun Guo; Wen Yao; Keke Li; Qi Zheng; Yongbiao Yu; Zhiwei Zhang; Yan Wang; Weigang Yao; Ju Wu; Huan Hu; Lingwei Hu; et al. (Plant Molecular Biology, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Transcriptomic analysis reveals the mechanism of ozone fumigation combined with polyethylene nanopackaging for delaying the browning and softening of mushrooms (Agaricus bisporus) - Biao Wang; Jianmin Yun; Weihong Guo; Jiawei Shen; Ting Wang; Fengyun Zhao; Yuling Qu; Liang Yao (Postharvest Biology and Technology, 2025)

Assessment of genetic diversity of Camellia yuhsienensis based on leaf structure and inter simple sequence repeat (ISSR) markers - Yuling Zou; Xiaoning Ge; Chao Yan; Qiuping Zhong; Danyang Chen; Zexin Chen; Yaqi Yuan; Hongyan Guo; Youcheng Zhou; Jinfeng Wang; Linqing Cao (Genetic Resources and Crop Evolution, 2024)

Design, construction and evaluation of collaborative bio-system of Vibrio fluvialis with Chlorella sorokiniana for treating actual printing and dyeing wastewater - Yuling Song; Lijun Wang; Xi Qiang; Menglin Guo; Wenhui Gu; Songcui Wu; Shan Gao; Xuehua Liu; Xiujun Xie; Quancheng Fan; Jing Zhang; Zengling Ma; et al. (Chemical Engineering Journal, 2024)

Enhanced generation and effective utilization of H2O2 for simultaneous aging of plastics in the C3N4/Vis-LED system with the addition of phenol - Xiaoman Zhang; Ting Zhang; Hongyang Guo; Shuqi Wan; Xiaodan Liu; Jianhui Sun; Yuling Zhao; Shuying Dong; Xianfa Su; Maohong Fan (Chemical Engineering Journal, 2024)

A transition from arbuscular to ectomycorrhizal forests halts soil carbon sequestration during subtropical forest rewilding - Ruiqiang Liu; Xuhui Zhou; Yanghui He; Zhenggang Du; Hongyang Chen; Yuling Fu; Liqi Guo; Guiyao Zhou; Lingyan Zhou; Jie Li; Hua Chai; Changjiang Huang; et al. (Science of The Total Environment, 2024)

Simultaneous removal of CTRX and Cr(Ⅵ) by CQDs-doped bifunctional molecular imprinted BiOCl/Bi3NbO7 photocatalyst: The enhanced selective performance and charge separation abilities - Huining Zhang; Yankui Xiao; Zongqian Zhang; Jianping Han; Zhiguo Wu; Zhiqiang Wei; Ying Zhu; Qi Guo; Lihong Tian; Yuling Tang (Journal of Environmental Chemical Engineering, 2024)

A new intracellularly regulated release pattern controlled by coordinated carrier cracking and drug release - Xinyue Zhang; Ye He; Zhiqi Wang; Ying Zhang; Wen Guo; Shuai Li; Xinyu Wang; Yuling Mao; Siling Wang (Chemical Engineering Journal, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Photocatalytic removal of ammonia nitrogen from water: investigations and challenges for enhanced activity - Huining Zhang; Yang Cao; Shaofeng Wang; Yuling Tang; Lihong Tian; Wenrui Cai; Zhiqiang Wei; Zhiguo Wu; Ying Zhu; Qi Guo (Environmental Science and Pollution Research, 2024)

Recent advances and prospects of persistent luminescent materials in public health applications - Yuechen Li; Conglin Guo; Jige Yuan; Xiaoxiao Yang; Haiwei Ji; Mingmin Wu; Li Wu; Yuling Qin (Chemical Engineering Journal, 2024)

A novel polyethylene nanopackaging combined with ozone fumigation delayed the browning and softening of Agaricus bisporus during postharvest storage - Biao Wang; Jianmin Yun; Chenguang Ye; Siya Xu; Weihong Guo; Fengyun Zhao; Yuling Qu; Yang Bi (Postharvest Biology and Technology, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Cr and N co-doped biochar driving controllable peroxydisulfate activation pathways to degrade tetracycline: Pyrrolic N inducing singlet oxygen generation - Lijun Guo; Liming Zhao; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2024)

Unveiling China’s natural and planted forest spatial–temporal dynamics from 1990 to 2020 - Kai Cheng; Haitao Yang; Hongcan Guan; Yu Ren; Yuling Chen; Mengxi Chen; Zekun Yang; Danyang Lin; Weiyan Liu; Jiachen Xu; Guangcai Xu; Keping Ma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Dysregulated PD-L2 is correlated with disease activity and inflammation in rheumatoid arthritis - Jian Xiong; Jie Yang; Yuling Sun; Yachun Chen; Yundi Guo; Cuiping Liu; Jing Sun (Immunogenetics, 2023)

Insights into electrogenerated intermediates and rapid screening of electrochemical reactions by surface-modified carbon fiber paper redox spray ionization mass spectrometry - Jiahui Bai; Mingmai Bao; Shanshan Wang; Tianlun Wen; Yuling Li; Jing Zhang; Tiansheng Mei; Yinlong Guo (Analytica Chimica Acta, 2023)

Condensation of STM is critical for shoot meristem maintenance and salt tolerance in Arabidopsis - Xiuwei Cao; Qingwei Du; Yahe Guo; Ying Wang; Yuling Jiao (Molecular Plant, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

Comparative Analysis of the Therapeutic Effects of Fresh and Cryopreserved Human Umbilical Cord Derived Mesenchymal Stem Cells in the Treatment of Psoriasis - Zhifeng Wang; Yifan Hu; Xiaoyu Wang; Youdong Chen; Danfeng Wu; Houli Ji; Cuicui Yu; Jingmeng Fang; Chunrong Pan; Lianjian Wang; Shouxin Wang; Yinhong Guo; et al. (Stem Cell Reviews and Reports, 2023)

Effects of different semen extenders on sperm motility and pregnancy rates in donkeys - Xuan Wu; Yuling Hu; Yajun Guo; Shenming Zeng (Journal of Equine Veterinary Science, 2023)

Effects of a novel plant growth regulator B2 on stalk quality and grain yield of winter wheat in North China - Chuanxi Peng; Yuling Guo; Guanmin Huang; Yingru Liu; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Plant and Soil, 2023)

How efficient is the environmental pollution control in China? - Ke Guo; Zhengyang Li; Yuequn Cao; Yuling Yang (Process Safety and Environmental Protection, 2023)

Chrome shaving-derived biochar as efficient persulfate activator: Ti-induced charge distribution modulation for 1O2 dominated nonradical process - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Science of The Total Environment, 2023)

Water deficit aggravated the inhibition of photosynthetic performance of maize under mercury stress but is alleviated by brassinosteroids - Yulou Tang; Junjie Zhang; Lijuan Wang; Hao Wang; Haochi Long; Liuyang Yang; Gengwei Li; Jiameng Guo; Yongchao Wang; Yuling Li; Qinghua Yang; Weiyu Shi; et al. (Journal of Hazardous Materials, 2023)

Hyperspectral imaging combined with chemometrics for rapid detection of talcum powder adulterated in wheat flour - Hong-Ju He; Yan Chen; Guanglei Li; Yuling Wang; Xingqi Ou; Jingli Guo (Food Control, 2023)

Toxicity of ceria nanoparticles to the regeneration of freshwater planarian Dugesia japonica: The role of biotransformation - Changjian Xie; Xiaowei Li; Lisha Hei; Yiqing Chen; Yuling Dong; Shujing Zhang; Shan Ma; Jianing Xu; Qiuxiang Pang; Iseult Lynch; Zhiling Guo; Peng Zhang (Science of The Total Environment, 2023)

Efficient determination of enantiomeric ratios of α-hydroxy/amino acids from fermented milks via ion mobility−mass spectrometry - Yuling Li; Li Zhang; Wenjian Sun; Kuofeng Tseng; Jing Zhang; Yinlong Guo (Food Chemistry, 2023)

Peroxydisulfate activation using Fe, Co co-doped biochar and synergistic effects on tetracycline degradation - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2023)

Synergistic effect of CoOx and Ni-Co alloy in Ni-Co/SAPO-11 catalysts for the deoxygenation of stearic acids - Dejiang Zheng; Delin Guo; Zhongxu Wang; Xiaosheng Wang; Yuling Shan; Xinmei Liu; Zifeng Yan; Shitao Yu; Yuxiang Liu (Chemical Engineering Journal, 2023)

Preparation of Functionalized Graphene Oxide Composite Spheres and Removal of Cu2+ and Pb2+ from Wastewater - Huining Zhang; Xingmao Liu; Lihong Tian; Yuling Tang; Zhongyu Shi; Yankui Xiao; Zhiguo Wu; Ying Zhu; Qi Guo; Zhangpu Peng (Water, Air, & Soil Pollution, 2022)

A method for evaluating drug penetration and absorption through isolated buccal mucosa with highly accuracy and reproducibility - Shuangqing Wang; Lei Liu; Saige Meng; Yuling Wang; Daofeng Liu; Zhonggao Gao; Along Zuo; Jianpeng Guo (Drug Delivery and Translational Research, 2022)

Synthesis and Luminescent Properties of 1,4,5-Triphenylimidazole‒Phenothiazine Fluorophores - Long Qian; Hongyan Yang; Yuling Zhao; Yongchun Guo; Tianzhi Yu (Journal of Fluorescence, 2022)

5-Aminolevulinic Acid-Hyaluronic Acid Complexes Enhance Skin Retention of 5-Aminolevulinic Acid and Therapeutic Efficacy in the Treatment of Hypertrophic Scar - Liya Yang; Huihui Deng; Yiman Chen; Yuling Chen; Ling Guo; Min Feng (AAPS PharmSciTech, 2022)

Human umbilical cord-derived mesenchymal stem cells ameliorate psoriasis-like dermatitis by suppressing IL-17-producing γδ T cells - Youdong Chen; Yifan Hu; Xue Zhou; Zihan Zhao; Qian Yu; Zeyu Chen; Yuanyuan Wang; Peng Xu; Zengyang Yu; Chunyuan Guo; Xilin Zhang; Yuling Shi (Cell and Tissue Research, 2022)

The comparative impact among different intensive statins and combination therapies with niacin/ezetimibe on carotid intima-media thickness: a systematic review, traditional meta-analysis, and network meta-analysis of randomized controlled trials - Hongwei Li; Xiaolin Xu; Liming Lu; Runlu Sun; Qi Guo; Qian Chen; Junjie Wang; Zhijian He; Yuling Zhang (European Journal of Clinical Pharmacology, 2021)

Comparisons of urea or ammonium on growth and fermentative metabolism of Saccharomyces cerevisiae in ethanol fermentation - Xinchao Yang; Yuling Yang; Jiadong Huang; Deen Man; Maihai Guo (World Journal of Microbiology and Biotechnology, 2021)

TMEM166 inhibits cell proliferation, migration and invasion in hepatocellular carcinoma via upregulating TP53 - Jiejie Yang; Bin Wang; Qian Xu; Yuling Yang; Lin Hou; Kan Yin; Qingming Guo; Yanan Hua; Li Zhang; Yixuan Li; Jinyu Zhang; Ning Li (Molecular and Cellular Biochemistry, 2021)

MiR-153 regulates cardiomyocyte apoptosis by targeting Nrf2/HO-1 signaling - Xianting Zhu; Yuling Zhao; Wei Hou; Ling Guo (Chromosome Research, 2019)

Abnormal Brain Structure and Function in First-Episode Childhood- and Adolescence-Onset Schizophrenia: Association with Clinical Symptoms - Yanhong Xia; Dan Lv; Yinghui Liang; Haisan Zhang; Keyang Pei; Rongrong Shao; Yali Li; Yan Zhang; Yuling Li; Jinghua Guo; Luxian Lv; Suqin Guo (Neuroscience Bulletin, 2019)

Molecular cloning and characterization of squalene synthase from Matricaria recutita L. - Xiaojuan Hou; Yuling Tai; Shuping Ling; Dahui Li; Chunxiao Guo; Jiameng Sun; Guifang Pan; Yi Yuan (Acta Physiologiae Plantarum, 2018)

Valosin-containing protein (VCP) promotes the growth, invasion, and metastasis of colorectal cancer through activation of STAT3 signaling - Qianfeng Fu; Yuling Jiang; Daxin Zhang; Xiuli Liu; Junfeng Guo; Jinlong Zhao (Molecular and Cellular Biochemistry, 2016)

Cloning and expression analysis of betalain biosynthesis genes in Amaranthus tricolor - Xueli Zheng; Shengcai Liu; Chunzhen Cheng; Rongfang Guo; Yukun Chen; Liyang Xie; Yuyuan Mao; Yuling Lin; Zihao Zhang; Zhongxiong Lai (Biotechnology Letters, 2016)

Spatio-temporal effects of fertilization in Anhui Province, China - Qinpu Liu; Yuling Guo; John P. Giesy (Environment, Development and Sustainability, 2015)

The Ph-3 gene from Solanum pimpinellifolium encodes CC-NBS-LRR protein conferring resistance to Phytophthora infestans - Chunzhi Zhang; Lei Liu; Xiaoxuan Wang; Jack Vossen; Guangcun Li; Tao Li; Zheng Zheng; Jianchang Gao; Yanmei Guo; Richard G. F. Visser; Junming Li; Yuling Bai; et al. (Theoretical and Applied Genetics, 2014)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)